MENINGKATKAN AKTIVITAS, KETERAMPILAN BERPIKIR KRITIS, DAN HASIL BELAJAR SISWA MENGGUNAKAN KOMBINASI MODEL PBL, STAD, DAN SNOWBALL THROWING PADA MUATAN IPAS DI SDN PANGERAN 1 BANJARMASIN - Qansha Saputri Hakim; Asrani (STKIP Subang, 2025)
The problems in this research is the low level of activity and critical thinking skills which result in low learning outcomes in the content of IPAS. The purpose of this research is to describe teacher activities, analyze the improvement of student activities, critical thinking skills, and learning outcomes. This research used Classroom Action Research which was carried out in 4 meetings. The subject of this research is 24 students in grade III of SDN Pangeran 1 Banjarmasin, in semester II of the 2024/2025 school year. The results of the research showed that the teacher's activities at meeting 4 had been carried out with the criteria of